Controlling murine and rat chronic pain through A(3) adenosine receptor activation - Chen, Zhoumou (Federation of American Societies for Experimental Biology, 2012)
Clinical management of chronic neuropathic pain is limited by marginal effectiveness and unacceptable side effects of current drugs. We demonstrate A(3) adenosine receptor (A(3)AR) agonism as a new target-based therapeutic strategy. The development of mechanoallodynia in a well-characterized mouse model of neuropathic pain following chronic constriction injury of the sciatic nerve was rapidly and dose-dependently reversed by the A(3)AR agonists: IB-MECA, its 2-chlorinated analog (Cl-IB-MECA), and the structurally distinct MRS1898. These effects were naloxone insensitive and thus are not opioid receptor mediated. IB-MECA was ≥1.6-fold more efficacious than morphine and >5-fold more potent. In addition, IB-MECA was equally efficacious as gabapentin (Neurontin) or amitriptyline, but respectively >350- and >75-fold more potent. Besides its potent standalone ability to reverse established mechanoallodynia, IB-MECA significantly increased the antiallodynic effects of all 3 analgesics. Moreover, neuropathic pain development in rats caused by widely used chemotherapeutics in the taxane (paclitaxel), platinum-complex (oxaliplatin), and proteasome-inhibitor (bortezomib) classes was blocked by IB-MECA without antagonizing their antitumor effect. A(3)AR agonist effects were blocked with A(3)AR antagonist MRS1523, but not with A(1)AR (DPCPX) or A(2A)AR (SCH-442416) antagonists. Our findings provide the scientific rationale and pharmacological basis for therapeutic development of A(3)AR agonists for chronic pain.—Chen, Z., Janes, K., Chen, C., Doyle, T., Bryant, L., Tosh, D.K., Jacobson, K.A., Salvemini, D. Controlling murine and rat chronic pain through A(3) adenosine receptor activation.